Camilo Barrionuevo, una Iglesia devorada por su propia sombra. Hacia una comprensión integral de la crisis de los abusos sexuales en la Iglesia Católica (2021)
This essay characterizes the construction of causal connections made by high school students in a didactic sequence centered on a historical problem and the use of evidence. Historical sense is elaborated considering agents, facts, and their causal relations. A mixed sequential qualitative-quantitative methodological approach is used to analyze a corpus of 119 causal connections. In the qualitative phase, we identify, through codes, the organizational mode of the causal connections (antecedent, foundation, consequent). In the quantitative phase, a multidimensional cluster analysis of these connections establishes 5 groups, coded according to the type and causal function of the historical factor. The results indicate that the foundation of the relationship between antecedent and consequent is scarce; Mostly the antecedent is attributed the causation. The historical factors used are: political-social entity (37 percent), historical concept (29.4 percent), historical actor (9.2 percent). The predominant causal functions are properties of agency and temporality